2022
DOI: 10.3390/met12101559
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of 3D Printing Parameters on Deformation by BP Neural Network Algorithm

Abstract: Traditional processing technology is not suitable for the requirements of advanced manufacturing due to the disadvantages of large repeated experiments, high cost, and low economic effect. As the latest additive technology, 3D printing technology has to deal with many issues such as process parameters and nonlinear mathematical models. A three-layer backpropagation (BP) artificial neural network with a Lavenberg–Marquardt algorithm was established to train the network and predict orthogonal experimental data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…More recently, artificial intelligence, machine learning, and deep learning have become integral components of 3D printing used in various aspects of additive manufacturing, including design optimization, predicting 3D printing parameters and process control, material development, part orientation, support generation, defect detection, quality control, etc. The application and importance of AI methods in 3D printing show promising advancements in eco-friendly applications, spanning from manufacturing to healthcare [81][82][83][84], e.g., in the machining industry [85], diagnosis systems to address anomalies and reducing printing errors [86,87], building reconstruction [83], predicting 3D-printed biomedical microneedle features [88,89], printable biomaterials [4,90,91], and automated and personalized production processes for pharmaceutics [92].…”
Section: History: Bridging Innovation With Environmental Sustainabilitymentioning
confidence: 99%
“…More recently, artificial intelligence, machine learning, and deep learning have become integral components of 3D printing used in various aspects of additive manufacturing, including design optimization, predicting 3D printing parameters and process control, material development, part orientation, support generation, defect detection, quality control, etc. The application and importance of AI methods in 3D printing show promising advancements in eco-friendly applications, spanning from manufacturing to healthcare [81][82][83][84], e.g., in the machining industry [85], diagnosis systems to address anomalies and reducing printing errors [86,87], building reconstruction [83], predicting 3D-printed biomedical microneedle features [88,89], printable biomaterials [4,90,91], and automated and personalized production processes for pharmaceutics [92].…”
Section: History: Bridging Innovation With Environmental Sustainabilitymentioning
confidence: 99%
“…where x n is the standardized data, x is the experimental data or the data after de-standardization; and x min and x max are the minimum and maximum values of the experiment, respectively [27]. The parameters of this BP neural network model are set as follows: trainlm of the Levenberg-Marquardt (L-M) optimization algorithm is chosen as the training function, the output layer neuron function uses purelin, the maximum training times is 1,000, the training target is 0.0001, and the learning rate is 0.01.…”
Section: Design Of the Bp Neural Networkmentioning
confidence: 99%
“…Their results showed that nozzle temperature was the most influential factor. Li et al [27] used the ANN algorithm to optimize processing parameters, such as initial layer thickness, printing temperature, printing speed, and filling rate, to avoid the deformation of the FDM 3D printed parts. The ANN model predicted the deformation values with a small error compared to the experimental values.…”
Section: Introductionmentioning
confidence: 99%